2014
DOI: 10.2478/afe-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

The Results of the Brass Refining Process in the Reducer Conditions

Abstract: This article contains information concerning of the analysis the possibility of defining refinery qualities of the slag based thermo-physical and thermo-dynamical data. It was showed the brass refining with the many-carbide reagents introduced in to the slag. The paper presents the results of the structure analysis of the brass after carbide slag refining in the industrial conditions. The results of the macrostructure analysis have confirmed the argument on high reducing effectiveness of manganese and aluminiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…The previous studies [1][2][3][4][5][6][7][8][9][10][11][12] allow drawing the conclusion that there is a strong correlation between the nature of the ingots structure and formation of electron phases such as BCC β phase and HCP ε phase in the case of exceeding particular elements solubility limits [1][2][3]. It has been observed that formation of β and ε is complex due to mutual interactions between particular elements, which in turn make difficulties in its clear description and led to huge interpretation discrepancies presented in the literature [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies [1][2][3][4][5][6][7][8][9][10][11][12] allow drawing the conclusion that there is a strong correlation between the nature of the ingots structure and formation of electron phases such as BCC β phase and HCP ε phase in the case of exceeding particular elements solubility limits [1][2][3]. It has been observed that formation of β and ε is complex due to mutual interactions between particular elements, which in turn make difficulties in its clear description and led to huge interpretation discrepancies presented in the literature [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is used in conjunction with the fluxes that correct physico -chemical properties of processed slag. However, in the light of the experience of the authors and other scientists [11][12][13][14][15], as well as theoretical analysis, that form of carbon reagent appears to be very inefficient. Reacting only with the agents of the melting atmosphere, solid carbonaceous/carbon does not dissolve itself, and, therefore, it does not react in the slag.…”
Section: Reagentsmentioning
confidence: 99%
“…The main physicochemical benefits of the application of such substances rely on their interaction with a properly prepared -both in terms of composition and properties of surface -active agents -slag layer [16,17]. Such an approach is a novelty in the pyrometallurgy of copper and currently is the object of patent application [18]. It enables the full usage of extraction reactions.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that many studies take the subject brass strictly defined composition, but they do not indicate how to obtain the final material, especially copper alloys -brasses [5][6][7]. Especially when raw materials for its production are of quite different composition [8][9][10][11][12]. It should also be noted that a well-designed algorithm of the metal charge for brasses creates the possibility of writing a computer program, like the application to calculate the viscosity using the Iida models from the program Slag.…”
Section: Introductionmentioning
confidence: 99%